The Relationship Between Cognitive Distortions and School Bullying in Jerusalem Suburbs’ Schools - Abdel Qader, Muhammad Ibrahim; rimawi, Omar Taleb (Dirasat: Human and Social Sciences, 2024)
Objectives: The study identifies the relationship between cognitive distortions and bullying in schools in the suburbs of Jerusalem. Methods: The study used a stratified sample of 250 students who study in schools located in the suburbs of Jerusalem and whose ages range from 15 to 18 years old. The Cognitive Distortions Scale and the School Bullying Scale were used as instruments for data collection after verifying their validity and reliability. Results: The results indicated that the mean score for cognitive distortions is moderate whereas the mean score for school bullying is low. Statistically significant differences were observed in the levels of cognitive distortions based on gender, with higher levels in males. Additionally, the results showed statistically significant differences in the levels of cognitive distortions and school bullying based on students’ grades, favoring students with lower grades. However, there were no statistically significant differences based on the grade level of participants. The study also identified a weak positive correlation between cognitive distortions and school bullying. Conclusion: By shedding light on the intricate relationship between cognitive distortions and school bullying, the study stresses the significance of developing educational and psychological strategies to address these challenges. Hence, it emphasizes the need for customized interventions in schools to deal with cognitive distortions and bullying, focusing on gender differences.